Pembuatan Aplikasi Inspeksi Harian Perangkat IT Berbasis Web Pada Rumah Sakit Islam hj. Siti Muniroh Tasikmalaya - Muhammad Haedar Ali (Jurnal Tika, 2024)
This research proposes designing a website-based daily inspection application for IT devices to improve information technology management at the Tasikmalaya Islamic Hospital. The research method uses a System Development Life Cycle (SDLC) approach which includes feasibility studies, planning, analysis, design, implementation, testing, implementation and maintenance. In the analysis stage, user needs are identified and application features are described, while system design includes architecture, user interface, and database structure. Implementation involves the use of specific programming languages and frameworks with thorough testing focused on sustainability, security, and reliability. The application was tested and implemented at the Tasikmalaya Islamic Hospital, with test data analyzed with quantitatively method. Research ethics includes consent and data security. The research schedule is prepared in detail. It is hoped that this research can make a positive contribution in improving the management of hospital IT equipment and become a reference for similar research in the future